(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In a Latin-American context in which their organizational processes and denunciations have national and internatio- nal relevance, movements and indigenous organizations claim theirs prehispanic and colonial past as an anchoring that gives legitimacy to their politics projects. What does it put in stake when they allude to indigenous memory, even if it takes in count its double link with the past and the pre- sent, and if it considers that whom put it into practices are subjects that share an ethnic condition? The purpose of this article is to contribute to the debate about the uses of the indigenous memory, reflecting about it since its tension with history and since the discussions about the subjectivity processes ́ and the ethnicity. These reflections are putted in dialogue with the experience of exercise of memory that is current carried out by the Zapatista movement in the Re- gion Altos in Chiapas State, México.